Polymorphisms in the human organic cation transporter and the multidrug resistance gene: correlation with imatinib levels and clinical course in patients with chronic myeloid leukemia. Issue 11 (November 2014) - Vine, Jacob; Cohen, Sara Bar; Ruchlemer, Rosa; Goldschmidt, Neta; Levin, Moshe; Libster, Diana; Gural, Alexander; Gatt, Moshe E.; Lavie, David; Ben-Yehuda, Dina; Rund, Deborah
Abstract: The optimal tyrosine kinase inhibitor for any individual patient with chronic myeloid leukemia (CML) is not predictable. Pharmacogenetic parameters and trough levels of imatinib (IM) have each been independently correlated with response. We therefore studied the human organic cation transporter (h OCT 1) and multidrug resistance ( MDR 1) single nucleotide polymorphisms (SNPs) and correlated these with IM levels and major molecular response (MMR) (3-log reduction) in 84 patients with CML, the first such study performed in Caucasians. We studied MDR 1 G2677T and C3435T, and for h OCT 1, C480G and A1222G. IM levels varied significantly with dose (< or > 400 mg/day) ( p = 0.038) and were significantly lower in 20 patients who lost MMR ( p = 0.042). Adjusting for dose, trough IM levels were not significantly correlated with SNPs. Patients with MDR 1 3435 TT had significantly longer times to MMR compared to CC/CT genotypes ( p = 0.047). Genotypes did not predict treatment failure when controlling for IM levels. We conclude that IM levels, but not the SNPs studied here, determine IM failure.